Uji Daya Hambat Ekstrak Cabai Hijau (Capsicum annum L) Terhadap Pertumbuhan Jamur Candida albicans Secara In Vitro - Annisa Amelia Lubis; Cut Sidrah Nadira; Wizar Putri Mellaratna (Publikasi Indonesia, 2022)
Fungal infection is one of the diseases that has experienced an increasing incidence in the world, especially Indonesia with its geographical condition as a country with a tropical climate with high temperature and humidity. One of the most common fungal infections is caused by the fungus Candida albicans. The incidence of antifungal resistance has become a health problem and has caused an increase in mortality. Efforts must be made to overcome this problem by utilizing secondary metabolite compounds found in green chili plants. Green chili (Capsicum annum L) contains secondary metabolites such as flavonoids, saponins, tannins, triterpenes/steroids and glycosides which act as antifungals. The purpose of this study was to test whether the extract of green chili (Capsicum annum L) could inhibit the growth of the fungus Candida albicans. The research method used is the posttest only control group design method. The effect of green chili extract was tested by diffusion method with concentrations of 2%, 4%, and 6% with a positive control of ketoconazole and a negative control of Dimethylsulfoxide (DMSO). Each treatment was carried out five times. The diameter of the inhibition zone was measured with a caliper. The results showed inhibition at all concentrations, namely 2% (7.9mm), 4% (10.6mm), 6% (11.2mm). The conclusion of this study was that the extract of green chili (Capsicum annum L) had the highest inhibitory power at a concentration of 6%.